Anxiety in public speaking and its contributing factors: the case of American degree foundation program students in UiTM / Ateff Yusof - Yusof, Ateff (2012)
The issue of lack of proficiency in speaking has been discussed widely in our country especially when it involves the future graduates. The fact that anxiety in speaking is ranked as one of the most feared activities to be done, has led to issues of employability since it is difficult to master this particular skill. Therefore, this study intended to examine the level of anxiety in public speaking and its contributing factors among the American Degree Foundation Program (ADFP) Students in Universiti Teknologi MARA. It also sought to identify the relationship between the factors that contribute to anxiety by Horwitz (1986); which are communication apprehension (CA), test anxiety (TA) and fear of negative evaluation (NE) on the level of anxiety noted by McCroskey (1970). In addition, the study also intended to identify several coping strategies to address anxiety in speaking. A sample of 210 ADFP students participated in this study. This study depended solely on quantitative method in gathering and analyzing the data where 3 sets of questionnaire were administered and all were adapted and amended to cater with the sociocultural and academic needs of the respondents. The study showed that most of the students possessed low level of anxiety in public speaking. The students experienced greater fear in terms of making mistakes when speaking which falls into the first factor which is communication apprehension out of the three factors (CA, TA and NE) identified that has contributed to anxiety in public speaking. It was also found that the levels of anxiety in public speaking and factors that contribute to it were statistically not related. Finally, teacher's role was found to be the most effective in overcoming speaking anxiety. Thus several recommendations and implication were drawn based on the findings.